Governing Gaza Bureaucracy, Authority, and the Work of Rule, 1917-1967 - Feldman, Ilana (Duke University Press, 2007)
Marred by political tumult and violent conflict since the early twentieth century, Gaza has been subject to a multiplicity of rulers. Still not part of a sovereign state, it would seem too exceptional to be a revealing site for a study of government. Ilana Feldman proves otherwise. She demonstrates that a focus on the Gaza Strip uncovers a great deal about how government actually works, not only in that small geographical space but more generally. Gaza's experience shows how important bureaucracy is for the survival of government. Feldman analyzes civil service in Gaza under the British Mandate (1917-48) and the Egyptian Administration (1948-67). In the process, she sheds light on how governing authority is produced and reproduced; how government persists, even under conditions that seem untenable; and how government affects and is affected by the people and places it governs.